2021
DOI: 10.3390/min11101140
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Fractal Dimension Calculation Technique to Determine the Shape of Selected Monchepluton Intrusion Crystals (NE Fennoscandia)

Abstract: Thirty-eight samples of minerals from Paleoproterozoic Layered PGE Intrusion Monchepluton, located in NE Fennoscandia, were tested. An automated computational technique was used which involved counting the sides superimposed on vectorized graphics using separated crystal boundaries. The results were obtained for olivine, orthopyroxene, clinopyroxene, and plagioclase. On this basis, an interpretation of the mineral box fractal dimension was made, along with an interpretation of its nature in the rock in which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The discussed intrusion is built up with pyroxenites and labradorites and accompanied by rocks containing chromites and iron-nickel and copper sulfide ores. Recent studies have also shown the presence of PGE mineralization in them [37,39].…”
Section: Characteristics Of the Geological Structure Of The Massifmentioning
confidence: 92%
See 4 more Smart Citations
“…The discussed intrusion is built up with pyroxenites and labradorites and accompanied by rocks containing chromites and iron-nickel and copper sulfide ores. Recent studies have also shown the presence of PGE mineralization in them [37,39].…”
Section: Characteristics Of the Geological Structure Of The Massifmentioning
confidence: 92%
“…In the meridian wing there are massifs from the north: Traviannaya, Kumuzhia, Nittis (called NKT). In the latitudinal wing from the west: Sopcha, Nyud, Poaz and lying south of them: Vurechuayvench [35][36][37][38]. The intrusion is surrounded from the north by archaic rocks of the Kola series and from the east and south by the Proterozoic formations of the Imandra-Varzuga belt.…”
Section: Characteristics Of the Geological Structure Of The Massifmentioning
confidence: 99%
See 3 more Smart Citations